2014
DOI: 10.3109/14397595.2013.854069
|View full text |Cite
|
Sign up to set email alerts
|

Remission in patients with active rheumatoid arthritis by tocilizumab treatment in routine clinical practice: results from 3 years of prospectively registered data

Abstract: In patients with RA, TCZ is highly effective for both biologics-naïve patients and patients previously exposed to biologics, achieving a high remission rate and drug continuation rate (68.2 %) in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…We have found an impressive frequency of 57.9% DAS28 remission at 6 months. These rates are higher than those observed in published RCTs (27% OPTION [ 27 ], 30.1% RADIATE [ 28 ], 39.9% ADACTA [ 15 ], and 40.4% ACT-RAY [ 13 ]) but similar to other observational register-based studies (39–58% DANBIO [ 20 ], 53.3% Michinoku Tocilizumab Study Group [ 29 ], 47.8% CABUKI [ 23 ], and 54.9% FRAB [ 21 ]). The EULAR response rates, based on DAS28, were also similar to those found in RCTs [ 13 , 15 , 27 ] and observational studies [ 20 , 26 ] that reported them.…”
Section: Discussionsupporting
confidence: 76%
“…We have found an impressive frequency of 57.9% DAS28 remission at 6 months. These rates are higher than those observed in published RCTs (27% OPTION [ 27 ], 30.1% RADIATE [ 28 ], 39.9% ADACTA [ 15 ], and 40.4% ACT-RAY [ 13 ]) but similar to other observational register-based studies (39–58% DANBIO [ 20 ], 53.3% Michinoku Tocilizumab Study Group [ 29 ], 47.8% CABUKI [ 23 ], and 54.9% FRAB [ 21 ]). The EULAR response rates, based on DAS28, were also similar to those found in RCTs [ 13 , 15 , 27 ] and observational studies [ 20 , 26 ] that reported them.…”
Section: Discussionsupporting
confidence: 76%
“…Overall, no TB cases were observed, though the 24-week duration of most studies may have led to underestimate the occurrence of active TB. However, also in the long-term trial, active TB cases did not occur [102, 109114]. Equally, no TB cases were recorded in the only one registry of 302 RA patients treated with TCZ [115].…”
Section: Resultsmentioning
confidence: 99%
“…A large retrospective cohort study reported that the retention rates for TCZ switched from ABT and for ABT switched from biologics other than TCZ were not significantly different 22) . Although the efficacy of TCZ as a subsequent biologic may be lower than that observed in treatment-naïve patients 16,22,23) , TCZ may be effective in patients who have received two or more biologics.…”
Section: Discussionmentioning
confidence: 93%
“…A previous randomized prospective study reported that the clinical response at week 12 could predict low disease activity at 52 weeks in patients treated with certolizumab pegol 24) . Another prospec- tive study reported that RA patients who exhibited a good response at 1 month after starting TCZ were 5.5 times as likely to achieve remission at 36 months 23) . These reports support the theory that early treatment response can predict the achievement of low disease activity in RA patients.…”
Section: Discussionmentioning
confidence: 99%